PENGETAHUAN TECHNOLOGICAL KNOWLEDGE (TK) GURU GEOGRAFI DI SMA KOTA PADANG - Fadila, Nurul; Rahmanelli, Rahmanelli (JURNAL BUANA, 2024)
The purpose of this research is to find out and analyze the knowledge of TK (technological knowledge) of geography teachers at SMA Padang city. Using this type of descriptive quantitative research. The research sample used by the geography teacher of Padang City Senior High School amounted to 30 respondents. Using the data obtained from the results of the geography teacher's questionnaire related to the technological knowledge of the geography teacher. Data collection techniques through questionnaires, interviews and documentation. As for data processing using the percentage test. Based on the research that has been done, the results show that the technological knowledge of the geography teachers of Padang City High School is very good with an average percentage of 86% which consists of the knowledge of geography teachers related to digital technology in the form of software and hardware, a percentage of 100%, the knowledge of geography teachers in applying the platform. google classroom with a percentage of 84%, knowledge of geography teachers in implementing the use of learning videos with a percentage of 84% and knowledge of geography teachers regarding the use of power point as a supportive learning medium with a percentage of 86%. Keywords: Geography Teacher, Knowledge, Technological Knowledge